Impact of Exercise Timing on Appetite Regulation in Individuals with Type 2 Diabetes - Heden, Timothy D. (Med Sci Sports Exerc, 2016)
PURPOSE: Exercise improves appetite regulation, but it is not known if pre or postmeal exercise more effectively improves appetite regulation in individuals with type 2 diabetes. For the first time, this study compared how pre and postmeal exercise alters appetite regulation in individuals with type 2 diabetes. METHODS: Twelve obese individuals with type 2 diabetes performed three different trials, all in a random order, in which they consumed a dinner meal with 1) no resistance exercise (RE), 2) premeal RE, or 3) postmeal RE beginning 45-min after dinner. A visual analog scale was used to assess perceived hunger and fullness and frequent blood samples were drawn for determination of acylated ghrelin, pancreatic polypeptide (PP), and peptide tyrosine tyrosine (PYY) concentrations. RESULTS: Premeal RE increased premeal perceived fullness, reduced perceived hunger, and reduced acylated ghrelin concentrations compared to the no RE and postmeal RE trial (P<0.05). In the postprandial period, both pre and postmeal RE reduced perceived hunger compared to no RE, while only postmeal RE reduced postprandial perceived fullness (P<0.05) compared to no RE. Pre or postmeal RE did not alter PYY concentrations. In both the premeal and postprandial period, RE reduced PP concentrations compared to no RE (P<0.05), but upon cessation of RE, PP concentrations rebounded to concentrations that were similar to no RE. CONCLUSION: Both pre and postmeal RE reduced perceived hunger and increased perceived fullness, effects that may help control food intake and aid in weight management efforts in individuals with type 2 diabetes.